Metabolic Syndrome in Hypothyroid Patients - Haque, R; Ferdousi, S; Ferdousi, SS; Rahman, W; Uddin, MN; Hoque, MM (Bangladesh Journal of Medical Biochemistry, 2015)
Thyroid functions affect metabolic syndrome (MetS) parameters including blood pressure, fasting plasma glucose, serum triglycerides and HDL-Cholesterol. But the relationship between MetS and thyroid functions is yet to be identified clearly. Metabolic syndrome is a state in which most features of hypothyroidism can be seen. The aim of the present study was to investigate the frequency of MetS in hypothyroid patients. Thirty one patients with overt hypothyroidism, 32 patients with subclinical hypothyroidism (SCH) and 58 euthyroid controls were enrolled in this study. NCEP-ATP III criteria was used to diagnose metabolic syndrome. Majority of the participants were in the age group of 30-40 years. Body mass index and waist circumference, blood pressure, fasting plasma glucose and serum triglycerides were found to be higher in hypothyroid patients compared to that of euthyroid controls (p<0.001). On the other hand serum HDL-C was found to be significantly lower in hypothyroid patients compared to that of euthyroid controls (p<0.001). Prevalence of MetS was 82.5% in the hypothyroid group and 27.6% in eythyroid controls (p<0.001). No significant difference was found between SCH (81.3%) and overt hypothyroid (86.7%) groups in respect to prevalence of MetS (p<0.05). The findings of the study suggest a need to investigate the presence of hypothyroidism during the management of MetS patients. DOI: http://dx.doi.org/10.3329/bjmb.v7i2.22414 Bangladesh J Med Biochem 2014; 7(2): 57-61